VD_FINDINFO Décision / 2015 / 82 vom 20. Februar 2014 - VD Tribunal cantonal (2014)
RETRAITVOIE DE DROIT, APPELCPP, DÉFENSE D'OFFICE, DÉPENS, PLAIGNANT, RECOURS JOINT | 135 CPP (CH), 386 al. 2 let. a CPP (CH), 428 al. 1 CPP (CH), 433 al. 1 CPP(CH), 433 al. 2 CPP (CH)